In vitro and in vivo degradation behaviors of thermosensitive poly(organophosphazene) hydrogels - Park, Mi-Ran; Cho, Chong-Su; Song, Soo-Chang (ELSEVIER SCI LTD, 2010)
Biodegradable and thermosensitive poly(organophosphazenes) with various substituents were synthesized and their hydrolytic degradation properties were investigated in vitro and in vivo. The aqueous solutions of all polymers showed a sol gel phase transition behavior depending on temperature changes. The side groups of polymers significantly affected the polymer degradation and accelerated hydrolysis of polymers in the order of carboxylic acid > depsipeptide > without carboxylic acid and depsipeptide. The increased gel strength led to the decreased hydrolysis rate. The polymer hydrogels with 750 Da of alpha-amino-omega-methoxy poly(ethylene glycol) were rapidly decreased by dissolution. The polymer degradation was also influenced by pH and temperature. The in vivo behaviors of mass decrease of the polymer hydrogels were similar with the in vitro results. These results suggest that the biodegradable and thermosensitive poly(organophosphazenes) hold great potentials as an injectable and biodegradable hydrogel for biomedical applications with controllable degradation rate. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: COPOLYMER AQUEOUS-SOLUTIONS; BLOCK-COPOLYMERS; DRUG-DELIVERY; TRIBLOCK; GELATION; GLYCOL); TEMPERATURE; POLYMERS; SYSTEMS